3D Microscope Imaging System based on the Transport of Intensity Equation - Hu, Tianqi (Transactions on Computer Science and Intelligent Systems Research, 2025)
This study aims to develop and implement a low-cost, high-resolution three-dimensional biological sample imaging system based on the light intensity transmission equation (TIE) technology to obtain the three-dimensional phase information of biological samples in a non-destructive way. The system can provide non-staining, real-time three-dimensional reconstruction images through a common optical path design, combined with a standard LED light source, CMOS sensor and optical components. The goal of this study is to provide a simpler and lower-cost imaging technology for biology, medicine and other related fields, especially for cell imaging, pathological analysis and other aspects.